Anti-Osteoclast Effect of Exportin-1 Inhibitor Eltanexor on Osteoporosis Depends on Nuclear Accumulation of IκBα–NF-κB p65 Complex - Chen, Junchun; Song, Dezhi; Xu, Yang; Wu, Liwei; Tang, Lili; Su, YuanGang; Xie, Xiaoxiao; Zhao, Jinmin; Xu, Jiake; Liu, Qian (Frontiers in Pharmacology, 2022)
Osteoporosis affects around 200 million people globally, with menopausal women accounting for the bulk of cases. In the occurrence and development of osteoporosis, a key role is played by osteoclasts. Excessive osteoclast-mediated bone resorption activity reduces bone mass and increases bone fragility, resulting in osteoporosis. Thus, considerable demand exists for designing effective osteoporosis treatments based on targeting osteoclasts. Eltanexor (Elt; KPT-8602) is a selective nuclear-export inhibitor that covalently binds to and blocks the function of the nuclear-export protein exportin-1 (XPO1), which controls the nucleus-to-cytoplasm transfer of certain critical proteins related to growth regulation and tumor suppression, such as p53, IκBα [nuclear factor-κB (NF-κB) inhibitor α] and FOXO1; among these proteins, IκBα, a critical component of the NF-κB signaling pathway that primarily governs NF-κB activation and transcription. How Elt treatment affects osteoclasts remains poorly elucidated. Elt inhibited the growth and activity of RANKL-induced osteoclasts in vitro in a dose-dependent manner, and Elt exerted no cell-killing effect within the effective inhibitory concentration. Mechanistically, Elt was found to trap IκBα in the nucleus and thus protect IκBα from proteasome degradation, which resulted in the blocking of the phosphorylation of IκBα and NF-κB p65 and the consequent inhibition of NF-κB activity. The suppression of NF-κB activity, in turn, inhibited the activity of two transcription factors (NFATc1 and c-Fos) essential for osteoclast formation and led to the downregulation of genes and proteins related to bone resorption. Our study thus provides a newly identified mechanism for targeting in the treatment of osteoporosis.